Analisis Pengaruh Harga, Pendapatan Konsumen, dan Jumlah Anggota Keluarga Terhadap Tingkat Permintaan Ikan Bandeng di Pasar Pabean Kota Surabaya - Muhammad Dimas Vebryan; Muhammad Yasin (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
There are several problems that affect the level of demand for milkfish in the Surabaya City Pabean Market, such as price factors, consumer income factors, and also the number of family members. This research was conducted to prove the effect of these problems on demand and is expected to be useful in overcoming the problems that occur. This research was formed from the quantitative method with hypothesis testing techniques carried out using multiple linear regression analysis. The population and sample in this study were 100 respondents. This study aims to test the theory, obtain facts, and show the relationship between variables. The data collection for this research took place at the Surabaya City Pabean Market. Prices, consumer income, and the number of family members have a positive and significant simultaneous effect on the demand for milkfish at the Surabaya City Pabean Market. Prices, consumer income have a positive and significant partial effect on the demand for milkfish at the Surabaya City Pabean Market, while the number of family members has an effect but not significant partial effect on the level of demand for milkfish at the Surabaya City Pabean Market.